2021
DOI: 10.1007/s13201-021-01415-3
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater physico-chemical properties and water quality changes in shallow aquifers in arid saline wetlands, Ouargla, Algeria

Abstract: Shallow aquifers are vulnerable to natural geogenic processes as well as anthropogenic influences, and this is especially apparent in desert regions. Within arid and hyperarid climates, evaporation is a controlling hydrologic process leads to an important increase in the concentration of dissolved minerals of both surface water and groundwater. In groundwater, this increase is not only dependent on shallow water table depth, but also on the hydraulic properties of sediments present within the unsaturated zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The study concluded that the main environmental factor affecting the wetland's water quality's spatial variance was salinity, which is a similar to what is observed in the present study [77]. A study by Medjani et al (2021) suggests that the management of water resources in arid and hyperarid areas, which are especially susceptible to anthropogenic influences and natural geogenic processes, is of high importance due to the effects of the environmental conditions [78]. A study aimed at understanding the causes of low water quality in the Amirkalayeh Wetland, a Ramsar Convention-listed wetland of international importance revealing that the wetland had undergone hyper-eutrophication due to a three-fold increase in salinity and a substantial rise in nutrient levels.…”
Section: Water-quality Index and Hazard Assessmentsupporting
confidence: 89%
“…The study concluded that the main environmental factor affecting the wetland's water quality's spatial variance was salinity, which is a similar to what is observed in the present study [77]. A study by Medjani et al (2021) suggests that the management of water resources in arid and hyperarid areas, which are especially susceptible to anthropogenic influences and natural geogenic processes, is of high importance due to the effects of the environmental conditions [78]. A study aimed at understanding the causes of low water quality in the Amirkalayeh Wetland, a Ramsar Convention-listed wetland of international importance revealing that the wetland had undergone hyper-eutrophication due to a three-fold increase in salinity and a substantial rise in nutrient levels.…”
Section: Water-quality Index and Hazard Assessmentsupporting
confidence: 89%
“…The concentration of Na + and Cl − (Figure 8) shows that most of the groundwater samples were projected, more or less, on the 1:1 slope line, indicating that the origin of these two elements in these waters was the dissolution of halite. However, four samples were Water-rock interactions are a crucial factor in understanding the changes in groundwater quality and can aid in determining the origin of groundwater [39,40]. To analyze the concentration and interrelationship of various major elements, the ratio of groundwater components is frequently employed.…”
Section: Groundwater Hydrochemistry and Mineralization Processesmentioning
confidence: 99%
“…The climate type is Hyper-arid desert (KÖPPEN classification BWh) having rare and irregular rainfall, with an annual average of 62.40 mm (Kharroubi et al 2022). Diurnal and nocturnal temperatures are variable, with an annual mean temperature ranging from 4.8°C to 43°C in January and July, respectively (Medjani et al 2021). Evapotranspiration rates are equally varied, ranging from 112 mm to 380 mm in the aforementioned months, as well (Chaouki et al 2014).…”
Section: Description Of the Study Areamentioning
confidence: 99%